Peningkatan Derajat Kesehatan Keluarga Melalui Kegiatan Inter Professional Collaboration (IPC) Mahasiswa Fakultas Kesehatan - Shalahuddin Al Madury; Nurcahyo, Elina Tasha Maharani; Yasminta, Firda; Mashanafi, Tisa Wandira; Kausar, Yusron; Najwani, Adinda Septi; Purnomo, Widya Tirta; Dohani, Priskila Clara (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2024)
The implementation of Clean and Healthy Life Behavior in the household environment has a very crucial role in forming healthy and productive individuals. PHBS in the household not only has an impact on the health of family members, but also contributes to improving the health of the community as a whole. Interprofessional Collaboration (IPC) is a partnership activity between health workers who have different professional backgrounds and work together to solve health problems and provide health services and achieve common goals through collaboration between IPC groups with families, patients and communities to provide comprehensive and high-quality care to achieve goals and provide mutual benefits. The IPC activity of the Faculty of Health which targeted the PHBS problem in Mr. S's family succeeded in improving the evaluation of the implementation of PHBS in the household environment, with a focus on education. The main problems identified were the smoking habits of family members, lack of understanding of the use of first aid kits, and education related to menopause. The intervention program succeeded in increasing family understanding through education, promotional media such as leaflets and posters, and direct training. The evaluation results showed an increase in knowledge of PHBS with a pretest measurement of 77.77 to 100 after education from the IPC team of the Faculty of Health.